2022
DOI: 10.1001/jamaophthalmol.2022.0223
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Artificial Intelligence–Based Retinopathy of Prematurity Screening

Abstract: IMPORTANCE Artificial intelligence (AI)-based retinopathy of prematurity (ROP) screening may improve ROP care, but its cost-effectiveness is unknown. OBJECTIVE To evaluate the relative cost-effectiveness of autonomous and assistive AI-based ROP screening compared with telemedicine and ophthalmoscopic screening over a range of estimated probabilities, costs, and outcomes. DESIGN, SETTING, AND PARTICIPANTSA cost-effectiveness analysis of AI ROP screening compared with ophthalmoscopy and telemedicine via economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Numerous studies have shown that both telemedicine and screening for ROP are highly beneficial for quality of life, cost saving, and cost-effectiveness. 8 As we move toward a model where AI may be part of our screening programs, Morrison and colleagues 9 suggest that AI-based screening for ROP may be more costeffective than telemedicine and ophthalmoscopy. They demonstrated in a probabilistic sensitivity analysis that autonomous AI screening was more than 60% likely to be cost- effective at all willingness-to-pay levels vs other modalities.…”
mentioning
confidence: 99%
“…Numerous studies have shown that both telemedicine and screening for ROP are highly beneficial for quality of life, cost saving, and cost-effectiveness. 8 As we move toward a model where AI may be part of our screening programs, Morrison and colleagues 9 suggest that AI-based screening for ROP may be more costeffective than telemedicine and ophthalmoscopy. They demonstrated in a probabilistic sensitivity analysis that autonomous AI screening was more than 60% likely to be cost- effective at all willingness-to-pay levels vs other modalities.…”
mentioning
confidence: 99%
“…For example, autonomous AI was as effective for and less costly (up to $34 for compared with telemedicine and $64 and $91 compared with ophthalmoscopy) for retinopathy of prematurity screening. 54 Also, research shows that AI-based tools produce cost savings if used as a strategy in screening colonoscopy, 55 and for breast cancer screening. 56 While this is encouraging, it cannot be generalized and need to be studied on a case by case basis.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study on the internet of things (IoT), machine learning is helping to speed up the growth of industrial supply chains, which saves both time and money. Morrison et al [ 280 ] developed a cost-effectiveness analysis of an AI-based solution [ 280 ] for retinopathy of prematurity (ROP) screening. The authors adapted the decision tree’s machine learning solutions and compared them against three different kinds of strategies such as ophthalmoscopy, telemedicine, and assistive AI with telemedicine review.…”
Section: Critical Discussionmentioning
confidence: 99%